Gallbladder stones and gallbladder polyps associated with increased risk of colorectal adenoma in men - Liu, Yen‐Ling; Wu, Jin‐Shang; Yang, Yi‐Ching; Lu, Feng‐Hwa; Lee, Chih‐Ting; Lin, Wan‐Ju; Chang, Chih‐Jen (Journal of gastroenterology and hepatology, 2018)
Background and Aims Most cases of colorectal cancer develop via an adenoma to carcinoma sequence. Gallbladder polyps share some risk factors with colorectal polyps. Little is known about the relationship between gallbladder diseases and different status of colorectal polyps by gender. This study was to investigate the association of gallbladder stones and polyps with colorectal adenomas by gender in a Taiwanese population. Methods A total of 7066 eligible subjects who underwent a total colonoscopy as a part of health check‐up between January 2001 and August 2009 were recruited. Colonoscopic findings were classified into polyp‐free, non‐neoplastic polyps and colorectal adenomas. Gallbladder stones and gallbladder polyps were diagnosed based on ultrasonographic findings. Results There was a significant difference in the status of colon polyps between subjects with and without gallbladder polyps. However, the status of colon polyps was not significantly different between subjects with or without gallbladder stones. After adjusting obesity, fasting plasma glucose, and other variables, there was a positive relationship between gallbladder polyps and colorectal adenomas (odds ratio [OR]: 1.396, 95% confidence interval [CI]: 1.115–1.747) but not non‐neoplastic polyps in all subjects. In men, gallbladder polyps (OR: 1.560, 95% CI: 1.204–2.019) and gallbladder stones (OR: 1.465, 95% CI 1.081–1.984) were positively associated with colorectal adenomas. In women, neither gallbladder polyps nor gallbladder stones were significantly related to colon polyps. Conclusions Both gallbladder polyps and gallbladder stones were associated with an increased risk of colorectal adenomas in men but not in women. Gender difference was significant for the association between gallbladder lesions and colorectal polyps.